ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA BERSTANDAR CAMBRIDGE ASSESSMENT INTERNATIONAL EDUCATION (CAIE) DITINJAU DARI KEMAMPUAN BERPIKIR KRITIS - Rahmah, Delia Safira; Yanti, Aning Wida; Sutini, Sutini (Journal of the Indonesian Mathematics Education Society, 2020)
The ability to solve problems is the ability to find a way out or answer by doing certain stages and understanding mature thinking. This study aims to describe the ability of Cambridge standard mathematical problem solving students who think critically high, medium, and low. This type of research is a qualitative descriptive study. The subjects in this study consisted of six students who answered correctly from class IX-1 MTs Bilingual Muslimat NU Pucang Sidoarjo. Data collection techniques are done by written tests and interviews. Data from written tests and interviews were analyzed according to indicators of critical thinking, then presented and analyzed using descriptive analysis. Based on the description and analysis of the data, it shows that students in high critical thinking categories in solving mathematical problems are of Cambridge standard, able to understand problems, plan and carry out problem solving, and re-examine problem solving. Students in the critical thinking category are currently solving Cambridge standard mathematical problems, tend to be less able to re-examine problem solving, but are able to understand problems, plan and implement problem solving. Students with low critical thinking categories in solving mathematics problems with Cambridge standards, tend to be less able in expressing planning and in re-examining problem solving, but are able to understand and carry out problem solving